Electronic Certificates as a Digital Legal Innovation in Indonesia (International Forum of Researchers and Lecturers, 2025)
The rapid advancement of digital technology has catalyzed significant legal transformations, particularly in the adoption of electronic documents and IT-based transactions. Among these innovations, electronic certificates serve as a critical instrument for verifying digital identities and ensuring the integrity of electronic documents. Regulated under Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), electronic certificates are legally recognized tools that support secure and efficient digital interactions. This article aims to examine the legal foundation, practical implementation, benefits, and challenges associated with electronic certificates in Indonesia. Employing a normative juridical approach, the research analyzes statutory regulations, academic literature, and field-based practices to provide a comprehensive understanding of the topic. The study reveals that electronic certificates possess a strong legal basis and offer substantial advantages in enhancing administrative efficiency, reducing paper-based processes, and promoting digital trust. However, the implementation of electronic certificates in Indonesia continues to face several challenges. These include inconsistencies in technical regulations, vulnerabilities in cybersecurity infrastructure, and limited digital literacy among the general population. Such barriers hinder the optimal utilization of electronic certificates and raise concerns regarding data protection, authentication reliability, and equitable access to digital services. The findings underscore the need for more robust regulatory frameworks, improved public education on digital literacy, and strengthened cybersecurity measures to support the widespread adoption of electronic certificates. Furthermore, collaboration among government institutions, private sector stakeholders, and civil society is essential to foster a secure and inclusive digital ecosystem. This research contributes to the ongoing discourse on legal modernization in Indonesia and offers strategic insights for policymakers seeking to align national digital governance with global standards.